A refractory element doped wear-resistant gradient HfMSiCN ceramic layer and preparation method thereof

By depositing a refractory element-doped gradient Hf(M)SiCN ceramic layer on the surface of Ti60 alloy, the problem of poor binding force of the existing ceramic coating in high temperature environment is solved, and a ceramic coating with high binding strength, excellent mechanical properties and high temperature wear resistance is achieved.

CN116121700BActive Publication Date: 2025-03-18NANJING UNIV OF AERONAUTICS & ASTRONAUTICS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211740550.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-18
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing ceramic coating has poor bonding force and is prone to oxidation and peeling in high-temperature friction and wear environments, which limits its application in high-temperature parts of marine ship engines.

Method used

Shuanghui plasma metallurgy technology is used to deposit a gradient Hf(M)SiCN ceramic layer doped with refractory elements on the surface of Ti60 alloy. Through sputtering deposition of high-purity grid-like targets, a surface Hf(M)SiCN deposition layer and an intermediate layer diffusion layer are formed to improve the bond strength between the coating and the substrate.

Benefits of technology

The bonding strength between the ceramic layer and the substrate is significantly improved, the mechanical properties and high-temperature wear resistance of the ceramic layer are improved, the high-temperature friction and wear rate is reduced, and the matrix material is protected.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121700B_ABST
    Figure CN116121700B_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements and a preparation method thereof, belonging to the technical field of Ti60 alloy surface modification, and adopts double-layer glow plasma technology to prepare the HfMSiCN gradient ceramic layer on the surface of Ti60 sample, and the selected refractory doping elements M are Ta, Zr, Nb, and Ti, respectively, and their types play a decisive role in the high-temperature wear resistance of the gradient HfMSiCN ceramic layer; grid-shaped high-purity Hf, Si, M, and C are used as sputtering targets, and the atomic ratio of each element in the target is 5-40%, argon is used as working gas, and nitrogen is used as reaction gas. The HfMSiCN gradient ceramic layer includes a deposition layer and a diffusion layer, wherein the diffusion layer is connected to the Ti60 substrate, and can improve the bonding strength between the coating and the substrate, improve the mechanical properties of the substrate, and reduce the high-temperature friction coefficient and wear rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of Ti60 alloy surface modification, and in particular relates to a refractory element-doped wear-resistant gradient HfMSiCN ceramic layer and a preparation method thereof. Background Art

[0002] With the continuous implementation of the strategies of building a strong maritime nation and a strong manufacturing nation, the development of marine resources cannot be separated from the renewal of equipment, and the high-temperature components of marine ship engines face a more severe service environment. Ti60 alloy has a wide range of application value in key parts of ships and carrier-based aircraft engines due to its high specific strength, excellent corrosion resistance and creep resistance, but its poor wear resistance and easy oxidation at high temperatures limit its further application in high-temperature parts of engines. Since the high-temperature friction and wear behavior begins on the surface of Ti60 alloy, a high-temperature resistant coating is prepared on the surface of Ti60 parts using surface modification technology, which enables the surface to overcome the above problems while retaining the original excellent performance of the base material.

[0003] Transition metal carbides (TMCs) and nitrides (TMNs) have a combination of covalent, ionic, and metallic bonds and are widely used as promising ceramic materials due to their excellent properties, including high hardness and melting point and excellent thermal stability. Many crystalline TMCs and TMNs in the rock salt structure are stable due to vacancies. In addition, transition metal carbonitrides (TMCNs, M = 3d, 4d, or 5d TM) exhibit superior properties such as high hardness (H), strength, and toughness than their corresponding pure carbides and nitrides (such as TaCN, NbCN, CrCN, and HfCN). Suxuan Du et al. studied TaC deposited by DC magnetron sputtering in the article "N dependent tribochemistry: Achieving superhard wear-resistant low-friction TaCxNy films" in the journal "Surface & Coatings Technology", Volume 328. x N y coating, in which C and N atoms occupy the interstitial positions of the Ta sublattice to form a NaCl-type TaC x N y Solid solution. Compared with TaC coating, TaC x N yThe coating shows better wear performance and minimal wear rate. However, the poor bonding between the sputtered deposited coating and the substrate further limits its application range, such as poor high-temperature oxidation resistance and easy peeling of the coating under ultra-high temperature wear conditions. In order to further improve the performance of TMCNs coatings. Many researchers have added modifying elements (Si, B) to TMCNs ceramic coatings to form composite ceramic coatings, obtaining composite oxide layers with low oxygen permeability, medium thermal expansion coefficient and high viscosity under high temperature wear to make up for the shortcomings of TMCNs coatings.

[0004] In recent years, various ceramic coatings containing N, B, C and other elements have been widely used. For example, Martin Matas et al. studied the Hf(M)SiBCN coating deposited by magnetron sputtering in the article "Dependence of characteristics of Hf(M)SiBCN(M=Y,Ho,Ta,Mo)thin films on the M choice:Ab-initio and experimental study" in the journal Acta Materialia, Volume 206, and showed that by selecting the appropriate type and composition of M, a hard film with good high temperature stability and high conductivity can be obtained at a lower temperature. However, the ceramic layer deposited by magnetron sputtering has poor bonding with the substrate, which limits its application range.

[0005] At present, the preparation methods of ceramic coatings mainly include thermal spraying technology, magnetron sputtering technology, and laser cladding technology. However, there are some disadvantages: although thermal spraying technology is simple to operate, has a short preparation cycle, and is not prone to deformation and stress, the coating has poor bonding strength with the substrate, thin thickness, and is prone to produce loose porous structures, making it difficult to meet the use requirements under high-speed and heavy-load environments; laser cladding technology is prone to cause metal droplets to splash during the preparation process due to its high instantaneous energy, and it is easy to form small particles on the coating surface, resulting in poor bonding between the coating and the substrate; although magnetron sputtering technology is widely used in coating preparation, the thickness of the prepared film is limited, the bonding strength with the substrate is insufficient, and it is difficult to ensure that the percentage of each element in the coating is equal to that in the target material. Therefore, there is an urgent need for a preparation method that can improve the bonding strength between the coating and the substrate, improve the comprehensive performance of the coating, and has a simple process. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides a refractory element-doped wear-resistant gradient Hf(M)SiCN ceramic layer and a preparation method thereof. The prepared ceramic layer is a gradient ceramic layer with high bonding strength, excellent mechanical properties, good high-temperature wear resistance, and controllable element types and compositions.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions:

[0008] A wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements. The ceramic layer is directly sputtered and deposited on the surface of a Ti60 alloy by a double glow plasma surface metallurgy technology using a high-purity grid-shaped target. The surface layer is a Hf(M)SiCN deposited layer with a thickness of 10-20 μm; the middle layer is a diffusion layer with a thickness of 3-10 μm; the diffusion layer and the Ti60 matrix are mutually diffused, and the content of Hf, M, Si, C, and N elements in the diffusion layer gradually decreases from the surface to the inside; the refractory doping element M selected each time is Ta, Zr, Nb or Ti, and the type of the refractory doping element M plays a decisive role in the high-temperature wear resistance of the gradient Hf(M)SiCN ceramic layer; argon is a working gas, and nitrogen is a reaction gas.

[0009] A method for preparing a refractory element-doped wear-resistant gradient HfMSiCN ceramic layer comprises the following steps:

[0010] Step 1: Matrix material pretreatment

[0011] The Ti60 alloy was processed into a sample with a size of 15 mm × 15 mm × 5 mm by wire cutting method, and then polished with 80-1000 mesh SiC waterproof sandpaper, and then polished on a polishing machine until it became a mirror surface; finally, it was placed in a beaker containing anhydrous ethanol for ultrasonic cleaning, and then dried for use;

[0012] Step 2: Clean and place samples

[0013] Before loading the sample into the furnace, the inner wall of the furnace body and the surface of the target were polished with fine sandpaper to remove the surface impurities and oxide film, and then wiped with non-woven cloth dipped in anhydrous ethanol. The pretreated sample and Hf(M)SiC grid-shaped target were placed in a double-layer glow plasma furnace. The target composition structure was arranged from left to right according to Hf / Si / M / C at equal intervals. The target-base distance was adjusted to 15-25mm. Ti60 alloy was used as the cathode, Hf(M)SiC grid-shaped target was used as the source, Ar was used as the working gas, N2 was used as the reaction gas, and grid-shaped high-purity Hf, Si, M, and C were used as the target, and the atomic ratio of each element was 5%-40%;

[0014] Step 3: Vacuum

[0015] Close the double-layer glow plasma furnace body, turn on the mechanical pump, and pump the gas in the furnace to below 2Pa;

[0016] Step 4: Add argon

[0017] Turn on the gas flow meter and valve control switch, and preheat the power supply at the same time; after the furnace reaches the corresponding vacuum degree, open the valve of the argon gas bottle and continue to pass argon gas for 20 minutes for cleaning;

[0018] Step 5: Sputtering

[0019] Adjust the gas pressure in the double-layer glow plasma furnace to 25Pa; when starting the glow, adjust the source voltage to 850V and the workpiece voltage to 420V;

[0020] Step 6: Preparation of Hf(M)SiCN gradient ceramic layer by double-glow plasma metallurgy technology

[0021] The gas pressure in the furnace is controlled at 25Pa, the source voltage is 800-900V, the workpiece voltage is 400-450V, and the Hf(M)SiCN ceramic layer is prepared by changing the type and content of M in the Hf(M)SiC grid-shaped target. Reactive nitrogen is introduced, and the flow ratio of argon and nitrogen is adjusted to 1:3.

[0022] Step 7: Keep warm

[0023] The preset insulation time is 4-7h;

[0024] Step 8, take out of the oven

[0025] After the heat preservation was completed, the alloy was cooled to room temperature to obtain a Ti60 alloy with a HfMSiCN gradient ceramic layer prepared on the surface.

[0026] Beneficial effects: The present invention provides a refractory element-doped wear-resistant gradient HfMSiCN ceramic layer and a preparation method thereof, which has the following advantages over the prior art:

[0027] (1) The present invention adopts double glow plasma metallurgy technology to prepare HfMSiCN gradient ceramic layer, and uses high-purity HfMSiC grid-shaped target as sputtering target, which can effectively improve the hollow cathode effect and the sputtering rate of the target. The type and composition of the selected refractory doping element M are controllable. Argon is used as the working gas and nitrogen is used as the reaction gas. Due to the presence of the diffusion layer between the prepared coating and the substrate, the bonding strength between the coating and the substrate can be significantly improved;

[0028] (2) The infiltration layer prepared by the present invention has a certain thickness of 10-40 μm, and a good metallurgical bond is formed between the coating and the substrate, thereby improving the mechanical properties of the substrate, as shown in Table 1, reducing the high-temperature friction coefficient and wear rate, and effectively protecting the substrate material under high-temperature friction and wear environment, wherein under high-temperature wear of 500°C, the substrate wear amount can be reduced by 50%;

[0029] (3) By adjusting the type and content of the M element in the grid-shaped target, the HfMSiCN ceramic coating can essentially solve the problem of poor membrane-substrate bonding by preparing a high-strength and tough coating, compared with the traditional method of alleviating the problem of poor membrane-substrate bonding by adding a support layer;

[0030] (4) The preparation method of the present invention is simple to operate, safe and environmentally friendly, and has low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the target material structure used in the present invention;

[0032] Figure 2 This is the SEM image of Example 4 of the present invention;

[0033] Figure 3 A schematic diagram of the coating structure prepared by the present invention;

[0034] In the figure, 1 is a deposition layer, 2 is a diffusion layer, 21 is an inward diffusion layer of the coating, and 22 is an outward diffusion layer of the substrate. DETAILED DESCRIPTION

[0035] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments:

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used are purchased from conventional stores unless otherwise specified; the quantitative experiments in the following examples are repeated three times, and the data are the average values ​​or average values ​​± standard deviations of the three repeated experiments.

[0037] Example 1

[0038] A wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements and a preparation method thereof, wherein the ceramic layer is directly sputtered and deposited on the surface of a Ti60 alloy by a double glow plasma surface metallurgy technology using a high-purity grid-shaped target, the surface layer is a HfMSiCN deposited layer with a thickness of 10-20 μm; the middle layer is a HfMSiCN diffusion layer with a thickness of 3-10 μm. The selected refractory doping element M is Ti, and the atomic ratio of each element is 5%-40%. Argon is the working gas, and nitrogen is the reaction gas. The HfMSiCN ceramic layer includes a deposited layer 1 and a diffusion layer 2, and the coating forms a good metallurgical bond with the Ti60 substrate.

[0039] The above ceramic layer preparation method comprises the following steps:

[0040] Step 1: Matrix material pretreatment

[0041] The Ti60 alloy was processed into a sample with a size of 15mm×15mm×5mm by wire cutting, and then polished with 80-1000SiC waterproof sandpaper, and then polished on a polishing machine until it became a mirror surface. Finally, it was placed in a beaker filled with anhydrous ethanol for ultrasonic cleaning, and then dried for later use;

[0042] Step 2: Clean and place samples

[0043] Before loading the sample into the furnace, the inner wall of the furnace body and the surface of the target were polished with fine sandpaper to remove the surface impurities and oxide film, and then wiped with non-woven cloth dipped in anhydrous ethanol. The pretreated sample and HfSiTiC grid-shaped target were placed in a double-layer glow plasma furnace. The target composition structure was arranged from left to right according to Hf / Si / Ti / C at equal intervals. The target-substrate distance was adjusted to 18 mm. Ti60 alloy was used as the cathode, HfSiTiC grid-shaped target was used as the source, Ar was used as the working gas, and N2 was used as the reaction gas.

[0044] Step 3, vacuuming: close the double-layer glow plasma furnace body, turn on the mechanical pump, and evacuate the gas in the furnace to below 2Pa;

[0045] Step 4, introduce argon: turn on the gas flow meter and valve-controlled switch, and preheat the power supply at the same time; after the furnace reaches a corresponding vacuum degree, open the valve of the argon gas bottle and continue to introduce argon for 25 minutes for cleaning;

[0046] Step 5, ignition sputtering: adjust the gas pressure in the double-layer glow plasma furnace to 20Pa; during ignition, adjust the source voltage to 800V and the workpiece voltage to 400V;

[0047] Step 6, preparation of HfTiSiCN gradient ceramic layer by double glow plasma metallurgy technology: the gas pressure in the furnace is controlled at 25Pa, the source voltage is 850V, the workpiece voltage is 420V, the reaction nitrogen is introduced, and the flow ratio of argon and nitrogen is adjusted to 1:3;

[0048] Step 7, heat preservation: the preset heat preservation time is 5h;

[0049] Step 8, taking out of the furnace: After the insulation is completed, cool to room temperature to obtain a Ti60 alloy with a HfTiSiCN gradient ceramic layer prepared on the surface. The prepared coating is a 14.15μm HfTiSiCN deposition layer 1, a 2.19μm thick diffusion layer 2 and a Ti60 titanium alloy from the outside to the inside.

[0050] Example 2

[0051] A wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements and a preparation method thereof, wherein the ceramic layer is directly sputtered and deposited on the surface of a Ti60 alloy by using a high-purity grid-shaped target material through a double glow plasma surface metallurgy technology, wherein the surface layer is a HfMSiCN deposition layer 1 with a thickness of 10-20 μm; and the middle layer is a HfMSiCN diffusion layer 2 with a thickness of 3-10 μm. The selected refractory doping element M is Ta, and the atomic ratio of each element is 5%-40%. Argon is the working gas, and nitrogen is the reaction gas. The HfMSiCN ceramic layer includes a deposition layer and a diffusion layer, and the coating forms a good metallurgical bond with the Ti60 substrate.

[0052] The preparation method comprises the following steps:

[0053] Step 1: Matrix material pretreatment

[0054] The Ti60 alloy was processed into a sample with a size of 15mm×15mm×5mm by wire cutting, and then polished with 80-1000SiC waterproof sandpaper, and then polished on a polishing machine until it became a mirror surface. Finally, it was placed in a beaker filled with anhydrous ethanol for ultrasonic cleaning, and then dried for later use;

[0055] Step 2: Clean and place samples

[0056] Before loading the sample into the furnace, the inner wall of the furnace body and the surface of the target were polished with fine sandpaper to remove the surface impurities and oxide film, and then wiped with non-woven cloth dipped in anhydrous ethanol. The pretreated sample and HfSiTaC grid-shaped target were placed in a double-layer glow plasma furnace. The target composition structure was arranged from left to right according to Hf / Si / Ta / C at equal intervals. The target-substrate distance was adjusted to 18 mm. Ti60 alloy was used as the cathode, HfSiTaC grid-shaped target was used as the source, Ar was used as the working gas, and N2 was used as the reaction gas.

[0057] Step 3, vacuuming: close the double-layer glow plasma furnace body, turn on the mechanical pump, and evacuate the gas in the furnace to below 2Pa;

[0058] Step 4, introduce argon: turn on the gas flow meter and valve-controlled switch, and preheat the power supply at the same time; after the furnace reaches a corresponding vacuum degree, open the valve of the argon gas bottle and continue to introduce argon for 25 minutes for cleaning;

[0059] Step 5, ignition sputtering: adjust the gas pressure in the double-layer glow plasma furnace to 20Pa; during ignition, adjust the source voltage to 800V and the workpiece voltage to 400V;

[0060] Step 6, preparation of HfTaSiCN gradient ceramic layer by double glow plasma metallurgy technology: the gas pressure in the furnace is controlled at 25Pa, the source voltage is 850V, the workpiece voltage is 420V, the reaction nitrogen is introduced, and the flow ratio of argon and nitrogen is adjusted to 1:3;

[0061] Step 7, heat preservation: the preset heat preservation time is 5h;

[0062] Step 8, taking out of the furnace: after the heat preservation is completed, cool to room temperature to obtain a Ti60 alloy with a HfTaSiCN gradient ceramic layer prepared on the surface; the prepared coating is a 14.15μm HfTaSiCN deposition layer, a 2.19μm thick diffusion layer and a Ti60 titanium alloy from the outside to the inside.

[0063] Example 3

[0064] A wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements and a preparation method thereof, wherein the ceramic layer is directly sputtered and deposited on the surface of a Ti60 alloy by a double glow plasma surface metallurgy technology using a high-purity grid-shaped target, the surface layer is a HfMSiCN deposited layer with a thickness of 10-20 μm; the middle layer is a HfMSiCN diffusion layer with a thickness of 3-10 μm. The selected refractory doping element M is Nb, and its type plays a decisive role in the high-temperature wear resistance of the gradient HfMSiCN ceramic layer. Argon is the working gas, nitrogen is the reaction gas, and the HfMSiCN ceramic layer includes a deposited layer and a diffusion layer, wherein the diffusion layer is connected to the Ti60 substrate.

[0065] The preparation method comprises the following steps:

[0066] Step 1: Matrix material pretreatment

[0067] The Ti60 alloy was processed into a sample with a size of 15mm×15mm×5mm by wire cutting, and then polished with 80-1000SiC waterproof sandpaper, and then polished on a polishing machine until it became a mirror surface. Finally, it was placed in a beaker filled with anhydrous ethanol for ultrasonic cleaning, and then dried for later use;

[0068] Step 2: Clean and place samples

[0069] Before loading the sample into the furnace, the inner wall of the furnace body and the surface of the target were polished with fine sandpaper to remove the surface impurities and oxide film, and then wiped with non-woven cloth dipped in anhydrous ethanol. The pretreated sample and HfSiNbC grid-shaped target were placed in a double-layer glow plasma furnace. The target composition structure was arranged from left to right according to Hf / Si / Nb / C at equal intervals. The target-substrate distance was adjusted to 18 mm. Ti60 alloy was used as the cathode, HfSiNbC grid-shaped target was used as the source, Ar was used as the working gas, and N2 was used as the reaction gas.

[0070] Step 3, vacuuming: close the double-layer glow plasma furnace body, turn on the mechanical pump, and evacuate the gas in the furnace to below 2Pa;

[0071] Step 4, introduce argon: turn on the gas flow meter and valve-controlled switch, and preheat the power supply at the same time; after the furnace reaches a corresponding vacuum degree, open the valve of the argon gas bottle and continue to introduce argon for 25 minutes for cleaning;

[0072] Step 5, ignition sputtering: adjust the gas pressure in the double-layer glow plasma furnace to 20Pa; during ignition, adjust the source voltage to 800V and the workpiece voltage to 400V;

[0073] Step 6, preparation of HfNbSiCN gradient ceramic layer by double glow plasma metallurgy technology: the gas pressure in the furnace is controlled at 25Pa, the source voltage is 850V, the workpiece voltage is 420V, the reaction nitrogen is introduced, and the flow ratio of argon and nitrogen is adjusted to 1:3;

[0074] Step 7, heat preservation: the preset heat preservation time is 5h;

[0075] Step 8, taking out of the furnace: after the heat preservation is completed, cool to room temperature to obtain a Ti60 alloy with a HfNbSiCN gradient ceramic layer prepared on the surface; the prepared coating is a 14.15μm HfNbSiCN deposition layer, a 2.19μm thick diffusion layer and a Ti60 titanium alloy from the outside to the inside.

[0076] Example 4

[0077] A wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements and a preparation method thereof, wherein the ceramic layer is directly sputtered and deposited on the surface of a Ti60 alloy using a high-purity grid-shaped target material through a double glow plasma surface metallurgy technique, wherein the surface layer is a Hf(M)SiCN deposited layer with a thickness of 10-20 μm; and the middle layer is a HfMSiCN diffusion layer with a thickness of 3-10 μm. The selected refractory doping element M is Zr, and its type plays a decisive role in the high-temperature wear resistance of the gradient HfMSiCN ceramic layer. Argon is the working gas, and nitrogen is the reaction gas. The HfMSiCN ceramic layer includes a deposited layer and a diffusion layer, wherein the diffusion layer is connected to the Ti60 substrate.

[0078] The preparation method comprises the following steps:

[0079] Step 1: Matrix material pretreatment

[0080] The Ti60 alloy was processed into a sample with a size of 15mm×15mm×5mm by wire cutting, and then polished with 80-1000SiC waterproof sandpaper, and then polished on a polishing machine until it became a mirror surface. Finally, it was placed in a beaker filled with anhydrous ethanol for ultrasonic cleaning, and then dried for later use;

[0081] Step 2: Clean and place samples

[0082] Before loading the sample into the furnace, the inner wall of the furnace body and the surface of the target were polished with fine sandpaper to remove the surface impurities and oxide film, and then wiped with non-woven cloth dipped in anhydrous ethanol. The pretreated sample and HfSiZrC grid-shaped target were placed in a double-layer glow plasma furnace. The target composition structure was arranged from left to right according to Hf / Si / Nb / C at equal intervals. The target-substrate distance was adjusted to 18 mm. Ti60 alloy was used as the cathode, HfSiZrC grid-shaped target was used as the source, Ar was used as the working gas, and N2 was used as the reaction gas.

[0083] Step 3, vacuuming: close the double-layer glow plasma furnace body, turn on the mechanical pump, and evacuate the gas in the furnace to below 2Pa;

[0084] Step 4, introduce argon: turn on the gas flow meter and valve-controlled switch, and preheat the power supply at the same time; after the furnace reaches a corresponding vacuum degree, open the valve of the argon gas bottle and continue to introduce argon for 25 minutes for cleaning;

[0085] Step 5, ignition sputtering: adjust the gas pressure in the double-layer glow plasma furnace to 20Pa; during ignition, adjust the source voltage to 800V and the workpiece voltage to 400V;

[0086] Step 6, preparation of HfZrSiCN gradient ceramic layer by double glow plasma metallurgy technology: the gas pressure in the furnace is controlled at 25Pa, the source voltage is 850V, the workpiece voltage is 420V, the reaction nitrogen is introduced, and the flow ratio of argon and nitrogen is adjusted to 1:3;

[0087] Step 7, heat preservation: the preset heat preservation time is 5h;

[0088] Step 8, taking out of the furnace: after the heat preservation is completed, cool to room temperature to obtain a Ti60 alloy with a HfZrSiCN gradient ceramic layer prepared on the surface; the prepared coating is a 14.15μm HfZrSiCN deposition layer, a 2.19μm thick diffusion layer and a Ti60 titanium alloy from the outside to the inside.

[0089] The coatings obtained in Examples 1 to 4 were subjected to bonding test and high temperature friction and wear test. The results showed that the HfTiSiCN, HfTaSiCN, HfNbSiCN and HfZrSiCN gradient ceramic coatings had good bonding performance with the substrate, as shown in Table 2 below. It can be seen that the bonding strength between the HfMSiCN gradient ceramic layer and the substrate is relatively high, and the weight loss of the substrate is significantly greater than that of the coating, indicating that the coating can effectively improve the wear resistance of the substrate and play a good protective role on the substrate. Among Examples 1 to 4, the coating obtained in Example 1 has the best comprehensive performance.

[0090] Table 1 Coating mechanical properties test

[0091] name Ti60 Example 1 Example 2 Example 3 Example 4 Microhardness(HV) 400.6 1203.1 890.5 1008.6 1429.0

[0092] Table 2 Bonding strength between coating and substrate and wear weight loss of Ti60 substrate and Hf(M)SiCN coating at different temperatures

[0093]

[0094] It should be noted that the structure of the HfTiSiCN gradient ceramic layer attached to the Ti60 surface prepared in Example 1 of the present invention is roughly the same as the structure of the HfMSiCN gradient ceramic layer attached to the Ti60 surface prepared in Examples 2-4, but the mechanical properties and wear resistance are greatly improved. Since the Ti-containing coating has a higher solubility in the Ti60 matrix elements, a thicker diffusion layer is formed, which makes the coating prepared in Example 1 have a higher bonding force.

[0095] The above are only preferred embodiments of the present invention. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the protection scope of the present invention.

Claims

1. A method for preparing a refractory element-doped wear-resistant gradient HfMSiCN ceramic layer, characterized in that: The following steps are involved: Step 1: Process the titanium alloy substrate into appropriate size as required, grind and polish it to a mirror finish, clean and dry it for later use; Step 2: remove impurities and oxide films in the double-layer glow plasma furnace and on the surface of the target material, place the treated target material and substrate into the double-layer glow plasma furnace, adjust the target-substrate distance, use grid-shaped high-purity Hf, Si, M, C targets, and arrange them at equal intervals from left to right according to Hf / Si / M / C; use the substrate as the cathode, the target material as the source, Ar as the working gas, N2 as the reaction gas, and M is Ta, Zr, Nb or Ti; Step 3: After the double-layer glow plasma furnace is evacuated, argon gas is continuously introduced for cleaning; Step 4: Adjust the gas pressure in the double-layer glow plasma furnace to 25Pa; start the glow to clean and preheat the double-layer glow plasma furnace; Step 5: The gas pressure in the furnace is controlled at 25 Pa, the source voltage is 800-900 V, the workpiece voltage is 400-450 V, and the reaction nitrogen is introduced. The HfMSiCN ceramic layer is prepared by changing the type and content of M in the HfMSiC grid-shaped target, and the temperature is kept for 4-7 hours; Step 6: After the heat preservation is completed, the alloy is cooled to room temperature to obtain a Ti60 alloy with a HfMSiCN gradient ceramic layer prepared on the surface.

2. The method for preparing the refractory element-doped wear-resistant gradient HfMSiCN ceramic layer according to claim 1, characterized in that: In step 1, the substrate is polished using 80-1000 mesh SiC waterproof sandpaper, and then placed on a polishing machine and polished to a mirror surface.

3. The method for preparing the refractory element-doped wear-resistant gradient HfMSiCN ceramic layer according to claim 1, characterized in that: The target-substrate distance in step 2 is 15-25 mm.

4. The method for preparing the refractory element-doped wear-resistant gradient HfMSiCN ceramic layer according to claim 1, characterized in that: When starting in step 4, adjust the source voltage to 850V and the workpiece voltage to 420V.

5. The method for preparing the refractory element doped wear-resistant gradient HfMSiCN ceramic layer according to claim 1, characterized in that: In step 5, the flow ratio of argon and nitrogen is adjusted to 1:

3.

6. The wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements according to any one of claims 1 to 5, characterized in that: The surface layer of the ceramic layer is a HfMSiCN deposition layer, and the inner layer is a diffusion layer connected to the substrate, and the diffusion layer and the substrate diffuse mutually; the content of Hf, M, Si, C, and N elements in the diffusion layer gradually decreases from the surface to the inside; and M is Ta, Zr, Nb or Ti.

7. The wear-resistant gradient HfMSiCN ceramic layer doped with refractory elements according to claim 6, characterized in that: The thickness of the deposition layer is 10-20 μm; the thickness of the diffusion layer is 3-10 μm.